A Conformational Analysis and Vibrational Spectroscopic Investigation on 1,2-bis(o-carboxyphenoxy) Ethane Molecule - Balcı, Kubilay; Yapar, Gönül; Akkaya, Yasemin; Koch, A.; Kleinpeter, E.; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
The minima on the potential energy surface of 1,2-bis(o-carboxyphenoxy)ethane (CPE) molecule in its electronic ground state were searched by a molecular dynamics simulation performed with MM2 force field. For each of the found minimum-energy conformers, the corresponding equilibrium geometry, charge distribution, HOMO-LUMO energy gap, force field, vibrational normal modes and associated IR and Raman spectral data were determined by means of the density functional theory (DFT) based electronic structure calculations carried out by using B3LYP method and various Pople-style basis sets. The obtained theoretical data confirmed the significant effects of the intra- and inter-molecular hydrogen bonding interactions on the conformational structure, force field, and group vibrations of the molecule. The same data have also revealed that two of the determined stable conformers, both of which exhibit pseudo-crown structure, are considerably more favorable in energy to the others and accordingly provide the major contribution to the experimental spectra of CPE. In the light of the improved vibrational spectral data obtained within the "SQM FF" methodology and "Dual Scale Factors" approach for the monomer and dimer forms of these two conformers, a reliable assignment of the fundamental bands observed in the experimental room-temperature IR and Raman spectra of the molecule was given, and the sensitivities of its group vibrations to conformation, substitution and dimerization were discussed. (C) 2011 Elsevier B.V. All rights
Keywords: glycol podands; salicylic acid; IR and Raman spectra; SQM FF; dual scale factors; density-functional theory; salicylic-acid; force-fields; scaling factors; raman-spectra; benzene molecule; aqueous-solution; hartree-fock; metal-ions; frequencies; salisilik asit; çift ölçek faktörleri; yoğunluk fonksiyonel teori; kuvvet alanları; ölçeklendirme faktörleri; benzen molekülü; sulu çözelti; metal iyonları; frekanslar